IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KOMUNIKASI MATEMATIS SISWA - Verra Novia Wardani; Senja Putri Merona (Universitas Muhammadiyah Ponorogo, 2017)
Mathematical communication is very important for mathematic learning. But, mathematic learning in school can’t increase mathematical communication. This research aims to describe the implementation of problem based learning to enhance students mathematical communication know increase of the mathematical communication through problem based learning in class VII MTs. Maarif Balong Ponorogo.This research is a classroom action research (CAR) conducted in two cycles. This research subject is the students of class VII B MTs. Ma’arif Balong Ponorogo. The data collection technique used is a test block, at the end of each cycle to measure mathematical communication and observation to evaluate the adherence of teachers and students activities. The results showed that mathematical communication increased from the first cycle to the second cycle after the implementation of problem-based learning model. This score average has been increased in accordance with the indicator of the success that was determined by the researchers. Based on the analysis of learning process through observation sheets of problem-based learning model showed that the average percentage activities of teachersand students activities increased from the first cycle to the second cycle. Keywords: Problem Based Learning, Mathematical Communication, Increase